1993
DOI: 10.1080/01635589309514269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rice bran hemicellulose on 1,2‐dimethylhydrazine‐induced intestinal carcinogenesis in fischer 344 rats

Abstract: The effect of rice bran hemicellulose (RBH) on 1,2-dimethylhydrazine- (DMH) induced intestinal carcinogenesis was studied in male Fischer 344 rats. Rats were fed a basal control diet or a diet containing 2% or 4% RBH at five weeks of age. At 6 weeks of age, all animals were given an intraperitoneal injection of DMH (20 mg/kg body wt) at weekly intervals for 20 weeks and autopsied 7 weeks after the last injection. The incidence of DMH-induced colon tumors was significantly lower in rats fed the 4% RBH diet than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The result described here in the Apc Min mouse is consistent with reports on the effect of rye bran (10% in the diet administered for 5 -6 weeks, Mutanen et al, 2000) and wheat bran (5 -20% for 7 -9 weeks, Hioki et al, 1997;Yu et al, 2001), which have previously been shown to reduce adenoma development in this model. Molecules in the rice bran fibre fraction, which may have contributed to inhibition of adenoma formation observed here in the Apc Min mouse, are the carbohydrates dextran-like a-glucan and arabinoxylan hemicellulose, both of which have previously been suggested to possess cancer chemopreventive properties (Takeo et al, 1988;Takenaka and Takahashi, 1991;Aoe et al, 1993). In principle there are three types of mechanism by which dietary fibre is thought to interfere with colorectal carcinogenesis (for review, see Young et al, 2005), and they may also be germane to rice bran fibre.…”
Section: Discussionmentioning
confidence: 92%
“…The result described here in the Apc Min mouse is consistent with reports on the effect of rye bran (10% in the diet administered for 5 -6 weeks, Mutanen et al, 2000) and wheat bran (5 -20% for 7 -9 weeks, Hioki et al, 1997;Yu et al, 2001), which have previously been shown to reduce adenoma development in this model. Molecules in the rice bran fibre fraction, which may have contributed to inhibition of adenoma formation observed here in the Apc Min mouse, are the carbohydrates dextran-like a-glucan and arabinoxylan hemicellulose, both of which have previously been suggested to possess cancer chemopreventive properties (Takeo et al, 1988;Takenaka and Takahashi, 1991;Aoe et al, 1993). In principle there are three types of mechanism by which dietary fibre is thought to interfere with colorectal carcinogenesis (for review, see Young et al, 2005), and they may also be germane to rice bran fibre.…”
Section: Discussionmentioning
confidence: 92%
“…AX which is not degraded or disintegrated in the upper gastrointestinal tract can be used as a component of selective drug delivery systems 171,172) . Water-soluble AX is able to control alcoholic liver disorders in rats 173) . Recently, in vitro fermentation tests have been performed on the algal (Palmaria palmata) xylan which represents a new dietary fiber source 174,175) .…”
Section: Biological Activitymentioning
confidence: 99%
“…Consumption of bran is reported to have a number of health benefits like laxative and stool bulking ability (Tomlin and Read 1988), anti-carcinogenic effect (Aoe et al 1993), and hypocholesterolemic effect for both full fat and defatted bran (Kahlon et al 1994;Hegsted and Windhauser 1993;Newman et al 1992).…”
Section: Introductionmentioning
confidence: 97%